Changes in locus wide repression underlie the evolution of Drosophila abdominal pigmentation. - Iván D Méndez-González; Thomas M Williams; Mark Rebeiz (PLoS Genetics, 2023)
Changes in gene regulation represent an important path to generate developmental differences affecting anatomical traits. Interspecific divergence in gene expression often results from changes in transcription-stimulating enhancer elements. While gene repression is crucial for precise spatiotemporal expression patterns, the relative contribution of repressive transcriptional silencers to regulatory evolution remains to be addressed. Here, we show that the Drosophila pigmentation gene ebony has mainly evolved through changes in the spatial domains of silencers patterning its abdominal expression. By precisely editing the endogenous ebony locus of D. melanogaster, we demonstrate the requirement of two redundant abdominal enhancers and three silencers that repress the redundant enhancers in a patterned manner. We observe a role for changes in these silencers in every case of ebony evolution observed to date. Our findings suggest that negative regulation by silencers likely has an under-appreciated role in gene regulatory evolution.